STUDI PENGARUH VARIASI JARAK NOZZLE TIP TERHADAP KEBUTUHAN GAS OXY-LPG DAN DURASI PADA PEKERJAAN PEMOTONGAN PELAT BADAN KAPAL SECARA MANUAL - Syahrul Setyo Pambudi; Tri Agung Kristiyono; Bagus Kusuma Aditya (JURNAL JALASENA, 2022)
The process of manually cutting plates with oxy-LPG gas is still widely used in shipyards and ship sub-contractors in Indonesia, both in the production of new building ships and repairs. In the cutting process, one of the factors that can affect the quality of cutting is the use of a tip nozzle distance. In the shipping industry, it is often found that the use of the tip nozzle distance in the process of manually cutting plates varies. The purpose of this study was to determine the effect of the nozzle tip distance on the need for oxy – LPG gas and the duration of cutting. This research method was carried out using the experimental method of cutting plates. Based on the results of data analysis, it is known that the higher the use of the nozzle tip distance, the need for oxy-LPG gas will increase while the cutting duration is not. The linear regression equation obtained between the distance of the tip nozzle and the oxygen requirement is Y = 0.0171X + 0.5357 and the tip nozzle distance with the LPG needs is Y = 0.0071X + 0.06, and the polynomial order 2 non-linear regression equation obtained between the tip nozzle distance and the cutting duration is Y = 0.9895X2 – 19.312X + 310.09 and the optimal distance of the tip nozzle is obtained at a distance of 9.758 mm with a cutting duration of 215.862 seconds.